IMPLEMENTASI ASESMEN DIGITAL BERBASIS QUIZIZ DALAM PENILAIAN PEMBELAJARAN BANGUN RUANG DI SEKOLAH DASAR - Zaini Tia Rizki Munte; Putri Febriani; Nisa Rahmadani; Cut Najwa Aulia; Eri Widyastuti (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The development of information and communication technology has encouraged the implementation of digital assessment in learning evaluation. One of the digital platforms that can be used in elementary school mathematics assessment is Quizizz. This study aimed to describe the implementation of Quizizz-based digital assessment in evaluating solid geometry learning among fifth-grade elementary school students. The research employed a descriptive qualitative method involving 20 fifth-grade students of SD Swasta Sialang in the 2025/2026 academic year. Data were collected through learning achievement tests administered via Quizizz and supported by documentation of assessment activities. The test consisted of 10 multiple-choice questions covering identification of solid figures, elements of solid geometry, volume, surface area, and contextual problem solving. Data were analyzed using data collection, reduction, presentation, and conclusion drawing techniques. The results showed that Quizizz-based digital assessment was implemented effectively and provided positive outcomes for students’ learning achievement. Of the 20 students, 17 students (85%) achieved the very high category, 1 student (5%) achieved the high category, 1 student (5%) achieved the moderate category, and 1 student (5%) achieved the low category. The findings indicate that Quizizz-based digital assessment can increase students’ engagement, motivation, and understanding of solid geometry concepts while facilitating teachers in conducting efficient and accurate learning evaluation.